Overview of MicroRNA Biogenesis, Mechanisms of Actions, and Circulation - O'Brien, Jacob; Hayder, Heyam; Zayed, Yara; Peng, Chun (Frontiers in Endocrinology, 2018)
MicroRNAs (miRNAs) are a class of non-coding RNAs that play important roles in regulating gene expression.  The majority of miRNAs are transcribed from genes into primary miRNAs and processed into precursor miRNAs and finally mature miRNAs. In most cases, miRNAs interact with the 3’ UTR of target mRNAs to induce mRNA degradation and translational repression. However, interaction of miRNAs with other regions, including the 5’ UTR, coding sequence, and gene promoters, have also been reported.  Under certain conditions, miRNAs can also activate translation or regulate transcription.  The interaction of miRNAs with their target genes is dynamic and dependent on many factors, such as subcellular location of miRNAs, the abundancy of miRNAs and target mRNAs, and the affinity of miRNA-mRNA interactions.  miRNAs can be secreted into extracellular fluids and transported to target cells via vesicles, such as exosomes, or by binding to proteins, including Argonautes. Extracellular miRNAs function as chemical messengers to mediate cell-cell communication.  In this review, we provide an update on canonical and non-canonical miRNA biogenesis pathways and various mechanisms underlying miRNA-mediated gene regulations.  We also summarize the current knowledge on the dynamics of miRNA action and on the secretion, transfer, and uptake of extracellular miRNAs.